2023
DOI: 10.1037/xge0001340
|View full text |Cite
|
Sign up to set email alerts
|

The wisdom of many in few: Finding individuals who are as wise as the crowd.

Abstract: Is forecasting ability a stable trait? While domain knowledge and reasoning abilities are necessary for making accurate forecasts, research shows that knowing how accurate forecasters have been in the past is the best predictor of future accuracy. However, unlike the measurement of other traits, evaluating forecasting skill requires substantial time investment. Forecasters must make predictions about events that may not resolve for many days, weeks, months, or even years into the future before their accuracy c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…We stress again, that the imputation does not require information about the ground truth and the past accuracy of the selected peers. Thus, it can be implemented as soon as the forecasting ends and does not require waiting for the revelation of the true state of the world (see also Himmelstein et al, 2023).…”
Section: Related Approachesmentioning
confidence: 99%
“…We stress again, that the imputation does not require information about the ground truth and the past accuracy of the selected peers. Thus, it can be implemented as soon as the forecasting ends and does not require waiting for the revelation of the true state of the world (see also Himmelstein et al, 2023).…”
Section: Related Approachesmentioning
confidence: 99%
“…A related variation, the expected Brier Score (EBS), is the average Brier score across each possible outcome weighted by the probability the crowd assigns to those outcomes (Himmelstein, Budescu & Ho, 2022) Bayesian Truth Serum: This method was originally developed by Prelec (2004) and also applies to both resolvable and unresolvable questions. Respondents are asked about their own best guess about the true answer, as well as their estimate of the crowd's average answer.…”
Section: Intersubjectivementioning
confidence: 99%
“…Himmelstein, Budescu and Ho (2022) expanded on this work in a study in which 175 forecasters made predictions about 11 events related to politics, economics, and public health. Each forecaster forecasted each event five times at three-week intervals leading up to event resolution.…”
Section: Intersubjectivementioning
confidence: 99%
“…However, it is not clear how many people one must retain during the aggregation process. Tetlock and Gardner ( 2016 ) and Himmelstein et al ( 2023 ) argue for the existence of superforecasters, who if identified can consistently beat the crowd. In Goldstein et al ( 2014 ), the authors find a decreasing relationship with the number of experts, where the performance decreases as more individuals are included.…”
Section: Introductionmentioning
confidence: 99%